Parametrization of Pedestrian Injuries and Its Utilisation in Proving Traffic Accidents Course - Nikita Bobrov1 , Ján Mandelík2 , Zuzana Nevolná3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This paper deals with the unique FORTIS system for parametrization of injuries, which allows one to make the scoring of injuries resulting from accidents, while it offers possibilities for its utilisation for the needs of the road transportation experts or biomechanics during the analysis of vehicle - pedestrian accident cases or for forensic biomechanical assessment of a course of other accidents. The work presents forensic investigation of fatal injuries of pedestrians and an assessment carried out via the FORTIS system in comparison with AIS. The output is a complex parametrization of accident consequences that can be used for the needs of traffic accident analysts and experts in other forensic sciences in calculations in a simulation program or using other forensic exact methods.